Adsorption of water on the pristine and defective semiconducting 2D CrPX3 monolayers (X: S, Se). (5th July 2021) - Xu, Sifan; Wu, Zhicheng; Dedkov, Yuriy; Voloshina, Elena
Abstract: The effect of vacancy and water adsorption on the electronic structure of semiconducting 2D trichalcogenide material CrP X 3 ( X : S, Se) is studied using state-of-the-art density functional theory (DFT) approach. It is found that chalcogen vacancies play a minor role on the electronic structure of CrP X 3 in the vicinity of the Fermi level leading to the slightly reduced band gap for these materials, however, inducing strongly localised defect states which are placed in the energy gap formed by the valence band states. Our DFT calculations show that the interaction of water molecules with CrP X 3, pristine and defective, can be described as physisorption and the adsorption energy for H2 O is insensitive to the difference between pristine and chalcogen-defective surface of trichalcogenide material. These results are the first steps for the theoretical description of the ambient molecules interaction with 2D semiconducting CrP X 3 material, that is important for its future experimental studies and possible applications.